CXCR3 expression defines a novel subset of innate CD8+ T cells that enhance immunity against bacterial infection and cancer upon stimulation with IL‐15. Issue 3 (2nd December 2014) - Oghumu, Steve; Terrazas, Cesar A.; Varikuti, Sanjay; Kimble, Jennifer; Vadia, Stephen; Yu, Lianbo; Seveau, Stephanie; Satoskar, Abhay R.
Abstract : Innate CD8 + T cells are a heterogeneous population with developmental pathways distinct from conventional CD8 + T cells. However, their biology, classification, and functions remain incompletely understood. We recently demonstrated the existence of a novel population of chemokine (C‐X‐C motif) receptor 3 (CXCR3)‐positive innate CD8 + T cells. Here, we investigated the functional properties of this subset and identified effector molecules and pathways which mediate their function. Adoptive transfer of IL‐15 activated CXCR3 + innate CD8 + T cells conferred increased protection against Listeria monocytogenes infection in susceptible IFN‐γ –/– mice compared with similarly activated CXCR3 – subset. This was associated with enhanced proliferation and IFN‐γ production in CXCR3 + cells. Further, CXCR3 + innate cells showed enhanced cytotoxicity against a tumor cell line in vitro. In depth analysis of the CXCR3 + subset showed increased gene expression of Ccl5, Klrc1, CtsW, GP49a, IL‐2Rβ, Atp5e, and Ly6c but reduced IFN‐γR2 and Art2b. Ingenuity pathway analysis revealed an up‐regulation of genes associated with T‐cell activation, proliferation, cytotoxicity, and translational initiation in CXCR3 + populations. Our results demonstrate that CXCR3 expression in innate CD8 + T cells defines a subset with enhanced cytotoxic potential and protective antibacterial immune functions. Immunotherapeutic approaches against infectious disease and cancer could utilize CXCR3 + innate CD8 + T‐cell populations as novel clinical intervention strategies.—Oghumu, S., Terrazas, C. A., Varikuti, S., Kimble, J., Vadia, S., Yu, L., Seveau, S., Satoskar, A. R., CXCR3 expression defines a novel subset of innate CD8+ T cells that enhance immunity against bacterial infection and cancer upon stimulation with IL‐15. FASEB J. 29, 1019–1028 (2015). www.fasebj.org